Synergetic Effect of 4-Phenylbutyric Acid in Combination with Cyclosporine A on Cardiovascular Function in Sepsis Rats via Inhibition of Endoplasmic Reticulum Stress and Mitochondrial Permeability Transition Pore Opening - Kuang, Lei; Zhu, Yu; Wu, Yue; Peng, Xiaoyong; Tian, Kunlun; Liu, Liangming; Li, Tao (Frontiers in Pharmacology, 2021)
Background: Sepsis/septic shock is a common complication in the intensive care unit and opening of the mitochondrial permeability transition pore (mPTP), as well as the endoplasmic reticulum stress (ERS), play important roles in this situation. Whether the combination of anti-ERS and anti-mPTP by 4-phenylbutyric acid (PBA) and cyclosporine A (CsA) could benefit sepsis is unclear. Methods: The cecal ligation and puncture-induced septic shock models were replicated in rats, and lipopolysaccharide (LPS)-challenged primary vascular smooth muscle cells (VSMCs) and H9C2 cardiomyocytes in vitro models were also used. The therapeutic effects of CsA, PBA, and combined administration on oxygen delivery, cardiac and vascular function, vital organ injury, and the underlying mechanisms were observed. Results: Septic shock significantly induced cardiovascular dysfunction, hypoperfusion, and organ injury and resulted in high mortality in rats. Conventional treatment including fluid resuscitation, vasoactive agents, and antibiotics slightly restored tissue perfusion, organ function in septic rats. Supplementation of CsA or PBA improved the tissue perfusion, organ function, and survival of septic shock rats. The combined application of PBA and CsA could significantly enhance the beneficial effects, compared with using PBA or CsA alone. Further study showed that PBA enhanced CsA-induced cardiovascular protection, which contributed to better therapeutic effects. Conclusion: Anti-ERS and anti-mPTP-opening by the combination of PBA and CsA was beneficial to septic shock. PBA enforced the CsA-associated cardiovascular protection and contributed to the synergetic effect.